Bugungi O’quvchilarimizning Sog’lom Tarbiyasida Xalq Og’zaki Ijodi Asosiy Manbaa Sifatida - Abdullayeva Barno Sayfutdinovna; Abrorxonova Kamolaxon Abrorxon qizi; Xudoyberganova Matluba Qulsoxatovna (Periodica Journal, 2024)
This article talks about the fact that folklore is the main source of healthy education for students and the meaning of ways to educate our youth through folklore
Keywords: Education; Health Education; Oral Creativity